TYPES OF ATTCAKS AND RESPONSES USED BY INDONESIA LAWAK KLUB (ILK) - Ersika Puspita Dani (Jurnal Mantik Penusa, 2015)
The objectives of this descriptive qualitative study were to discover: (1) the types of attacks in televised debate program and to describe how the addressee respond to the attacks. The data were obtained from the downloaded episodes and then were transcribed. The data were comedians’ utterances in ILK Comedy Program from the topics of Bullying. The data were identified, analyzed and categorized based on Culpeper’s (2011). The findings of the study showed that: 1) there were 39 expressions (43.4%) for attacks on quality face, 23 expressions (25.5 %) for attacks on social identity face, 12 expressions (13.3 %) for attacks on equity rights, and 16 expression (17.8 %) for attacks on assotiation rights, and the types of response which consist of 18 espressions (20 %) for no response, 21 expressions (23.3 %) for accepting the attacks, 39 expressions (43.4 %) for countering defensively, and 12 expressions (13.3 %) for countering offensively. Therefore, the most dominant type of responses to the attacks are accepting the attacks and countering defensively. Meanwhile, the least is countering offensively. 2) Over 16 categories created, there were 16 categories found in the data. They are (1) attacks on quality face – no response, (2) attacks on quality face – accepting response, (3) attacks on quality face – countering defensively, (4) attacks on quality face – countering offensively, (5) attacks on social identity face – no response, (6) attacks on social identity face – accepting response, (7) attacks on social identity face – countering defensively, (8) attacks on social identity face – countering offensively, (9) attacks on equity rights – no response, (10) attacks on equity rights – accepting response, (11) attacks on equity rights – countering defensively, (12) attacks on equity rights – countering ofensively, (13) attacks on association rights – no response, (14) attacks on association rights – accepting response, (15) attacks on association rights – countering defensively, and (16) attacks on association rights – countering offensively.Overall, the data showed that impoliteness was used as effective communication strategy to entertain the audience; therefore, it is expected that related parties such as television producers and comedians, notice the effect of the impoliteness use to the society as well as the need of parental guide for the show. Keywords: types of attacks, responses, impoliteness